Feasibility of Cell-Free DNA Collection and Clonal Immunoglobulin Sequencing in South African Patients With HIV-Associated Lymphoma. (2021) - Vogt, Samantha L.; Patel, Moosa; Lakha, Atul; Philip, Vinitha; Omar, Tanvier; Ashmore, Philippa; Pather, Sugeshnee; Haley, Lisa M.; Zheng, Gang; Stone, Jennifer; Mayne, Elizabeth; Stevens, Wendy; et al.
Abstract : PURPOSE: Diagnosis of AIDS lymphoma in low-resource settings, like South Africa, is often delayed, leaving patients with limited treatment options. In tuberculosis (TB) endemic regions, overlapping signs and symptoms often lead to diagnostic delays. Assessment of plasma cell-free DNA (cfDNA) by next-generation sequencing (NGS) may expedite the diagnosis of lymphoma but requires high-quality cfDNA. METHODS: People living with HIV with newly diagnosed aggressive B-cell lymphoma and those with newly diagnosed TB seeking care at Chris Hani Baragwanath Academic Hospital and its surrounding clinics, in Soweto, South Africa, were enrolled in this study. Each participant provided a whole blood specimen collected in cell-stabilizing tubes. Quantity and quality of plasma cfDNA were assessed. NGS of the immunoglobulin heavy chain was performed. RESULTS: Nine HIV+ patients with untreated lymphoma and eight HIV+ patients with TB, but without lymphoma, were enrolled. All cfDNA quantity and quality metrics were similar between the two groups, except that cfDNA accounted for a larger fraction of recovered plasma DNA in patients with lymphoma. The concentration of cfDNA in plasma also trended higher in patients with lymphoma. NGS of immunoglobulin heavy chain showed robust amplification of DNA, with large amplicons (> 250 bp) being more readily detected in patients with lymphoma. Clonal sequences were detected in five of nine patients with lymphoma, and none of the patients with TB. CONCLUSION: This proof-of-principle study demonstrates that whole blood collected for cfDNA in a low-resource setting is suitable for sophisticated sequencing analyses, including clonal immunoglobulin NGS. The detection of clonal sequences in more than half of patients with lymphoma shows promise as a diagnostic marker that may be explored in future studies.